(untitled) (Scientific journal of the Fergana State University, 2026)
The FAR1-RELATED SEQUENCE1 (FAR1) and FAR-RED ELONGATED HYPOCOTYL3 (FHY3) transcription factor family, which originated from transposases, plays a crucial role in light signal transduction and various physiological and developmental processes, including seed germination, photomorphogenesis, flowering, and stress responses. To date, members of this gene family have been bioinformatically and functionally characterized in several vegetable, industrial, and ornamental crops. In this study, we identified homologs of the FHY3/FAR1 gene family in Gossypium hirsutum using the genome of the Texas Marker-1 (TM1) model variety and compared them with representatives of the FHY3/FAR1 gene family from Arabidopsis thaliana, potato (Solanum tuberosum), poplar (Populus trichocarpa Torr. & Gray), and tea (Camellia sinensis). Through comparative bioinformatic analyses, a total of 149 FHY3/FAR1 genes were identified in cotton. Among them, 89 homologous genes were confirmed through sequence comparison. Amino acid and coding DNA sequence (CDS) analyses revealed that all identified transcripts possess characteristic domains of the FHY3/FAR1 gene family, including MULE, SWIF, and FAR1/FHY3 DNA-binding domains. These findings provide a foundation for further studies on the evolution and functional roles of the FHY3/FAR1 gene family in cotton, and contribute to understanding the molecular mechanisms governing cotton growth and development.